A Biomimetical Dynamic Window Approach to Navigation for Collaborative Control. - Ramos-Jiménez, Gonzalo Pascual; Ballesteros-Gómez, Joaquín; Urdiales-García, Amalia Cristina; Martínez Velasco, Antonio B. (IEEE, 2017)
—Shared control is a strategy used in assistive plat forms to combine human and robot orders to achieve a goal. Col laborative control is a specific shared control approach, in which user’s and robot’s commands are merged into an emergent one in a continuous way. Robot commands tend to improve efficiency and safety. However, sometimes, assistance can be rejected by users when their commands are too altered. This provokes frustration and stress and, usually, decreases emergent efficiency. To improve acceptance, robot navigation algorithms can be adapted to mimic human behavior when possible. We propose a novel variation of the well-known dynamic window approach (DWA) that we call biomimetical DWA (BDWA). The BDWA relies on a reward func tion extracted from real traces from volunteers presenting different motor disabilities navigating in a hospital environment using a rol lator for support. We have compared the BDWA with other reactive algorithms in terms of similarity to paths completed by people with disabilities using a robotic rollator in a rehabilitation hospital unit. The BDWA outperforms all tested algorithms in terms of likeness to human paths and success rate.
Keywords: Robótica; Indoor navigation; Rehabilitation robotics; Robot learning